Federalism and different concepts of nation in Argentina 1830-1880 - Bravo, María Celia (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article aims at analyzing several concepts of the word Nation adopted by Argentinean Federalism during the period of 1830-1880, in the light of the shifting powers between provinces and the emerging Central State. Depending on this,the word ‘federal’ could refer to the dissipation process of the colonial order, identiied by the retroversion of sovereignty over the cities, or it could describe a federal movement intended to unify and consolidate. Both deinitions were virtuously related to the meaning of the word Nation.